Perbahasan sosialis di Parlimen Malaysia analisa terhadap belanjawan 2009 - Jeyakumar Devaraj (Parsosma Enterprise, 2009)
Parliamentary discussion concerning the 2009 Malaysian budget from a socialist perspectives.